Mental health inequalities among underserved groups: evidence from the 2021 Census Northern Ireland - McKenna, Sarah; Ross, Emma; Maguire, Aideen (International Journal of Population Data Science, 2025)
Objectives Mental health inequalities are a pressing public health issue, but population-level data on mental health need among underserved groups (USGs) is lacking. This census-based record linkage study examines mental ill health across seven USGs in Northern Ireland (NI) to support the effective formulation of policy and health service provision. Methods Using the Northern Ireland Mortality Study (NIMS), which links 2021 Census records to area-level measures and death registrations, we identified 1,489,210 individuals aged 16 years or older. The presence of a chronic mental health condition (measured through the Census) was examined among ethnic minorities, Irish Travellers, sexual minorities (lesbian, gay, bisexual and other (LGB+)), religious minorities, migrants, informal carers, and those with limited English language proficiency. Logistic regression models quantified the likelihood of mental ill health for each USG relative to the majority reference group adjusting for age, sex, income deprivation, socioeconomic status, limiting long-term health condition and general health. Results Overall, 10.5% (156,504) of the cohort reported a chronic mental health condition. Among minority populations, increased risk of mental ill health was evident for females from a Mixed ethnic background (adjusted Odds Ratio (aOR 1.19 [95% CI 1.07-1.33] vs White)), Irish Travellers (aOR=1.46 [95% CI 1.29-1.66] vs non-Irish Traveller), migrants from the rest of the UK or Republic of Ireland (aOR=1.07 [95% CI 1.04-1.09] vs born NI), those with no religious affiliation (aOR=1.32 [95% CI 1.30-1.35] vs Catholic), and informal carers (20+ hours, aOR=1.13 [95% CI 1.11-1.16] vs no unpaid care). People from the LGB+ group appear to be at particularly high risk of chronic mental ill health (aOR=3.25 [95% CI 3.15-3.35] vs heterosexual). Conclusion The NI Census provides valuable insights into the mental health of USGs who are often missing from other available data. Risk of mental ill health varies significantly for some USGs relative to majority populations. Findings emphasize the need for service providers and policymakers to address mental health inequalities among USGs.